Destination Branding and Tourist Engagement in the Era of Experiential Tourism - Sherena Anodhea Eka Pramudita; Anggun Wida Prawira; Khodijah Asshofiah; Nourma Alivia Zahra El Rakhim (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The increasing dominance of experiential tourism has transformed destination branding from a symbolic identity tool into a dynamic mechanism for fostering sustained tourist engagement. Despite growing scholarly attention, limited empirical clarity remains regarding how experiential destination branding translates into behavioral, relational, and governance-related outcomes through tourist engagement. This study adopts an empirical, quantitative research design to examine the relationships among experiential destination branding, tourist engagement, and downstream behavioral and sustainability outcomes. Data were collected from domestic and international tourists who visited experience-oriented destinations within the previous twelve months using a structured questionnaire, and analyzed through Structural Equation Modeling to assess both measurement and structural relationships. The findings demonstrate that experiential destination branding exerts a strong positive effect on tourist engagement, which mediates the influence of branding on satisfaction, revisit intention, advocacy behavior, and participatory practices. The results further reveal that engaged tourists exhibit heightened sustainability awareness and greater support for destination governance initiatives, indicating that engagement functions as a soft governance mechanism alongside market-oriented outcomes. The study contributes to tourism management literature by empirically positioning tourist engagement as a relational bridge connecting experiential branding, behavioral value creation, and sustainable destination development in the contemporary tourism landscape.